Comparative adsorption profiles of basal lamina proteome and gingival cells onto dental and titanium surfaces. (June 2018) - Abdallah, Mohamed-Nur; Abughanam, Ghada; Tran, Simon D.; Sheikh, Zeeshan; Mezour, Mohamed A.; Basiri, Tayebeh; Xiao, Yizhi; Cerruti, Marta; Siqueira, Walter L.; Tamimi, Faleh
Graphical abstract: Abstract: Titanium (Ti) dental implants are susceptible to bacterial infections and failure due to lack of proper epithelial seal. Epithelial cells establish a strong epithelial seal around natural teeth by the deposition of basal lamina (BL) proteins that adsorb on the tooth surface. This seal can even be re-established onto cementum or dentin following injury or periodontal therapy. However, it is unclear how tooth surfaces promote this cell attachment and protein adsorption. Understanding the interactions between BL proteins and epithelial cells with dentin and Ti will facilitate the development of implant surfaces that promote the formation of an epithelial seal and improve the success of periodontal therapy and wound healing on natural teeth. To study these interactions, we used a surface proteomic approach to decipher the adsorption profile of BL proteins onto Ti and dentin, and correlated these adsorption profiles with in vitro interactions of human gingival fibroblasts and epithelial cells. Results showed that dentin adsorbed higher amounts of key BL proteins, particularly laminin and nidogen-1, and promoted more favorable interactions with epithelial cells than Ti. Next, dentin specimens were deproteinized or partially demineralized to determine if its mineral or protein component was responsible for BL adsorption and cell attachment. Deproteinized (mineral-rich) and partially demineralized (protein-rich) dentin specimens revealed BL proteins (i.e. laminin and nidogen-1) and epithelial cells interact preferentially with dentinal proteins rather than dentin mineral. These findings suggest that, unlike Ti, dentin and, in particular, dentinal proteins have a selective affinity to BL proteins that enhance epithelial cell attachment. Statement of Significance: It is remains unclear why natural teeth, unlike titanium dental implants, promote the formation of an epithelial seal that protects them against the external environment. This study used a surface screening approach to analyze the adsorption of proteins produced by epithelial tissues onto tooth-dentin and titanium surfaces, and correlate it with the behaviour of cells. This study shows that tooth-dentin, in particular its proteins, has a higher selective affinity to certain adhesion proteins, and subsequently allows more favourable interactions with epithelial cells than titanium. This knowledge could help in developing new approaches for re-establishing and maintaining the epithelial seal around teeth, and could pave the way for developing implants with surfaces that allow the formation of a true epithelial seal.